Synchrony and diachrony : a dynamic interface - Giacalone Ramat, Anna, 1937-; Mauri, Caterina, 1981-; Molinelli, Piera (Studies in language companion series ;, 2013)
In Extreme Southern dialects of Italy, complement clauses can appear in three different ways: (1) with the infinitive; (2) with modo + ind. (in Salentino quod + ind.); (3) with ca/chi + ind. Dependent finite clauses headed by modo/quod replace the infinitive particularly when the matrix predicate is a verb expressing will, wish, aim or intention. This replacement, which represents a syntactic calque from Italo-Greek varieties, finished to involve also the verb potere 'can', in a different way from Italo-Greek, where it is is the only verbal form which never appears in this.